(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Educators and policymakers have faced persistent challenges in closing achievement gaps between low-income and minority students in urban school districts and their peers with greater financial resources and from majority backgrounds. Human Resources Leaders must work to ensure that they are implementing strategic actions that will result in recruiting and retaining highly effective teachers and principals in our most disadvantaged school districts. This qualitative study examines the perceptions of three Human Resources Leaders from urban school districts engaged in a cohort learning experience about strategic actions they have implemented to improve teacher and leader quality in their school districts. The cohort experience, with the pseudonym of the Urban Schools Human Resources Improvement Project, involved ten school districts in a learning experience over a three-year period of time. The findings from this study identify the high impact actions of three Human Resources Leaders from urban school districts engaged in the Urban Schools Human Resources Improvement Project.